1988
DOI: 10.1002/ptr.2650020108
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity and gastrointestinal irritant effect of Croton penduliflorus seed oil in mice

Abstract: The effects of three dosage levels (250 mg/kg, 600 mg/kg, 800 mg/kg per 0s) of Croton pendulijporus seed oil were studied in mice. The mice were dosed with the oil suspension in 5% Tween 20 through oral intubation. Five mice from each dosage group were slaughtered at 3 h, 9 h and 24 h post-treatment with the oil. Various segments of the gastro-intestinal tract and visceral organs including the liver, lung, kidney, spleen, testis, adrenal glands and heart were examined grossly and tissue sections were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Croton species play relevant roles in the treatment of diseases by traditional healers and, as such, a comprehensive study of their chemical constituents is vital for validation of their traditional medicinal uses as well as exploring new potential sources of novel therapeutics. Croton Penduliflorus (Euphorbiaceae) has been found to indicate histopathological and gross changes in the duodenum, stomach, colon, and ileum (Asuzu et al, 1988). It is also considered to possess anti-venom, antimicrobial, anti-paralytic, anti-tumor, and rubefacient activities (Tania et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Croton species play relevant roles in the treatment of diseases by traditional healers and, as such, a comprehensive study of their chemical constituents is vital for validation of their traditional medicinal uses as well as exploring new potential sources of novel therapeutics. Croton Penduliflorus (Euphorbiaceae) has been found to indicate histopathological and gross changes in the duodenum, stomach, colon, and ileum (Asuzu et al, 1988). It is also considered to possess anti-venom, antimicrobial, anti-paralytic, anti-tumor, and rubefacient activities (Tania et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Acute toxicity study of the seed oil at the doses of 250, 600 and 800 mg/kg in mice adversely affected certain organs of the animals (Azuzu and Chineme, 1988;Ojokuku et al, 2010). Despite all these studies which focussed mainly on the seed oil, there is none in the open scientific literature that has addressed the laxative effect of the ethanolic extract of C. penduliflorus seeds in rats.…”
Section: Introductionmentioning
confidence: 99%
“…It forms a major component of herbal contraceptives, abortifacient and anti-fibroid concoctions used in the local treatment of fibroids (Adjanohoun et al, 1996;Odesanmi et al, 2006). Asuzu and Chineme (1987), Asuzu et al (1988Asuzu et al ( , 1989 indicated that Croton penduliflorus seed oil had irritant effect on the gastrointestinal tract and induced adverse effects on the internal organs including liver and kidneys and central nervous system of mice. It also induced pharmacological effects on isolated smooth and skeletal muscles and blood pressure.…”
Section: Introductionmentioning
confidence: 99%